Dynamics of access and utilization of information on urban waste management by the community in Banjarmasin City - Najmi Fuady; Muhammad Iqbal; Sarifah Nur Isra Jairina; Mina Azahra; Annisa Aulia Nur (Library and Archive, Universitas Gadjah Mada, 2026)
Introduction. The closure of the Basirih landfill led to waste accumulation and the emergence of illegal dumpsites across Banjarmasin, where limited public access to policy information hindered effective waste management. This study examined how urban residents accessed information on waste management policy and how openness to information shaped behavioral change. Research Methods. A qualitative exploratory case study was employed, involving 15 informants from five affected districts. Data Analysis. Data were collected through in-depth interviews, observation, and documentation, and then analyzed thematically using the information grounds (IG) and diffusion of innovations (DOI) frameworks. Results. Findings showed that residents accessed information predominantly through informal spaces rather than formal channels such as village office briefings or neighborhood meetings. Information openness influenced behavioral change when messages were delivered by credible sources, easy to understand, and reinforced by visible local examples. Behavioral change remained constrained by the absence of technical guidance, digital literacy gaps, and limited infrastructure. Conclusion. In a waste management crisis, informal channels functioned as the primary information infrastructure through which formal policy was validated. The effectiveness of behavioral innovation diffusion depended on information openness and trust in local sources, not on the intensity of formal government outreach alone.